ARABIC-ENGLISH CODE MIXING IN #ABTALKS PODCAST ON ANAS UKHASH’S YOUTUBE CHANNEL - Khairunnisa, Nadiya; Nur Hopipah, Rianty; Nurwahidah, Najma; Ja’far, Birrul Mandala Ja’far; Zalfa, Agrina (Fakultas Ilmu Budaya, Universitas Padjadjaran, 2025)
Sociolinguistics pays considerable attention to the bilingualism. As a communication strategy, bilingual communities often employ code-mixing. Nowadays, code-mixing can be observed in interactions on digital platforms. This study aims to describe the types and factors of code-mixing by Arabic speakers in the #ABtalks podcast. The types are analyzed using Muysken’s theory and the factors using Hoffman-Troike’s theory. The method used for this research is descriptive qualitative analysis through direct element division (BUL) and referential pairing. The findings indicate 119 insertion data, 78 alternation data, and 24 data of congruent lexicalization. The use of code-mixing is influenced by several factors, such as lexical needs, emphasizing something, filling and connecting sentences, repetition for clarification, talking about certain topics, refining requests or orders, and the efficiency of a conversation. This research contributes to the understanding of bilingual speech patterns and reflects the linguistic flexibility of Arabic in the digital world.